The Role Of Business Model Innovation, Trust, And Customer Commitment In Sme Business Growth (A Study On Gamelan Craft Sme Business In Special Region Of Yogyakarta) - Bayu Aji Laksono; Al Hasin (Cita konsultindo, 2025)
The purpose of this study was to investigate how customer loyalty, trust, and innovative business models affect the expansion of small and medium enterprises (SMEs), especially the gamelan craft SME